Efektivitas Penggunaan Social Media dalam Meningkatkan Kesadaran Masyarakat terhadap Potensi Promosi Kelurahan Pedurungan Lor - Vega, Jane Amalia; Septianing, Rena Trinita; Maheswara, Respati Dzaky; Chintya, Bernika; Aina, Mualina Nur; Putra, Ardiansyah Cahya; Pinem, Agusta Praba Ristadi (TEMATIK, 2024)
Social media has become a global phenomenon that affects various aspects of human life, including for the umkm in the Pedurungan lor Village. In carrying out promotions on Social Media, the public is required to create content that is relevant and interesting to get consumers’ attention. However, due to the minimum and lack of knowledge of the MSMEs in Pedurungan Lor regarding the importance of planning and implementing appropriate promotion strategies on social media, the team proposing community service, the Department of Communication Science, Faculty of Information and Communication Technology, University of Semarang, was moved to do community service to Msmes in Pedurungan Lor Village. , Semarang City, with the title “RISING UP UMKM”. To provide knowledge and skills in terms of promotion on social media, and develop more targeted promotion strategies, improve the quality of content to expand reach.
Keywords: UMKM; Promotion; Social Media